Upaya Meningkatkan Hasil Belajar Administrasi Pajak Melalui Penerapan Model Pembelajaran Kooperatif Dengan Problem Based Learning (Pbl) Materi Perhitungan Ppn dan Ppnbm Siswa Kelas XII.AKL.1 SMK Negeri 1 Dumai Tahun Ajaran 2022/2023 - Warni Warni (Peneliti.net, 2023)
This classroom action research aims to improve student learning outcomes in the subject of Value Added Tax (VAT) and Luxury Goods Sales Tax (LGST) for students of Class XII.AKL.1 at State Vocational High School 1 Dumai in the academic year 2022/2023. This is done through the implementation of the Cooperative Learning Model with Problem-Based Learning (PBL). The subjects of this research are 36 students of Class XII.AKL.1 at State Vocational High School 1 Dumai in the academic year 2022/2023. This class was chosen as the research subject because the students' learning outcomes in the previous topic were lower compared to other classes. Out of the Minimum Mastery Criteria (KKM) set by the school, which is 75, there were 15 students (41.67%) who met the criteria. The research results show that in the first cycle, the number of students who passed was 21 (58.33%), and it increased to 32 (88.89%) in the second cycle. The students' average activity level in the first cycle was 69.25%, categorized as good, and in the second cycle, it increased to 94.26%, categorized as very good. The teacher's activity level in the first meeting of the first cycle was 26 (52%), which increased to 34 (68%) in the second meeting. It further increased to 41 (82%) in the first and last meetings of the second cycle, and 47 (94%) in the second meeting. The overall research results indicate that the implementation of the Cooperative Learning Model with Problem-Based Learning (PBL) effectively improves student learning outcomes.